Real-life stories of online harassment — and how scientists got through it. (18th October 2018) - Gewin, Virginia
Certain fields draw frequent attacks on social media and other digital platforms. Three scientists explain how they navigate the minefields. Certain fields draw frequent attacks on social media and other digital platforms. Three scientists explain how they navigate the minefields.